Subsídios da ouvidoria do Hospital Universitário Walter Cantídio da Universidade Federal do Ceará para a gestão do complexo hospitalar - Falcão, Rosa Ângela de Brito (2010)
This is a study of the management of a university hospital of the Federal University of Ceará, from manifestations of Service Ombudsman. This is a descriptive, exploratory and based on documentary analysis of primary data service. The goal was to make a diagnosis of management HUWC / UFC, based on demonstrations brought by citizens seeking our service ombudsman. Moreover, the study has also been proposed to identify, based on descriptive analysis, the demonstrations that have caused changes in the model of hospital management, to enable corrective action of a collective nature. That said, it was possible to see the results of the Office of Ombudsman on the outcome of individual and collective lawsuits. The study obtained data relevant to the events of the period from 2006 to 2008. It was thus necessary to classify them into complaints, suggestions, information, complaint and compliment. Were also established three levels of management for grouping of expressions: hospital management, management of the public and academic management. The statistical results obtained allowed the descriptive analysis of the universe, the same being formed in 698 events. The research showed that despite the complexity of bureaucratic procedures and funding from the sphere of hospital management, is almost identical percentage of the riots between this sphere and the sphere of the SUS, 51% and 48% respectively. By contrast the manifestations of academic management constituted 5% of the universe. As for the results achieved by the Ombudsman, although the prevalence of satisfactory answers, there was growth in the demonstrations unanswered and individual solutions, which enhances the necessary reflection of the formal institutionalization of the ombudsman in Public Administration with constitutional provision. In relation to changes in management, the study suggests the need to legitimize the group manager grants the Ombudsman, in order to improve their management processes with a focus on citizen perception of the user